Dielectric and Piezoelectric Properties of CuO-Doped (Na0.5K0.5)0.94Li0.06NbO3 Lead-Free Ceramics - Tian, Changan; Liu, Junliang; Yin, Qiyi; Xie, Jinsong; Wang, Cunyang; Ji, Bifa; Sun, Guangen (Asian Journal of Chemistry, 2013)
(Na0.5K0.5)0.94Li0.06NbO3-x (mol %) CuO ceramics were prepared by a solid state reaction approach and their dielectric and ferroelectric properties were evaluated by conventional methods. The high piezoelectric properties of d33 = 115Pc/N, kp = 0.259, er = 697, tan d = 2.9 % were obtained for the (Na0.5K0.5)0.94Li0.06NbO3 ceramics containing 1 mol % CuO sintered at 1035 ºC for 2 h. Therefore, the (Na0.5K0.5)0.94Li0.06NbO3 ceramics containing a small amount of CuO are a good candidate material for lead-free piezoelectric ceramics.